DIVERSIFIKASI PRODUK OLAHAN IKAN LELE UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT DESA SIGUMURU - Rambe, Muhammad Rahman; Nasution, Alvi Sahrin; Pohan, Rizky Febriani (Universitas Mataram, 2025)
Catfish is a type of freshwater fish with high economic value, both in terms of sales value and nutritional value. Furthermore, this fish is easy to grow, with a high protein content, soft, white meat, and affordable prices. However, suboptimal cultivation results in low yields, which reduces the income of catfish farmers. One effort to increase the income of catfish farmers is through diversification of processed catfish products (catered fish paste, catfish meatballs, and catfish satay). This activity aims to improve the knowledge and skills of the Sigumuru Village community in processing catfish into a variety of processed products. Furthermore, this activity can also increase the income of the Sigumuru Village community. The methods used in this activity were location surveys, socialization, demonstrations, marketing, and monitoring. The participants of this activity were the Fish Cultivation Group (FCG)